The Basic stages of biography of prominent ship engineer V.P. Kostenko: Historiography of problem - O. V. Sandurska (History of science and technology, 2014)
This article is devoted to the main aspects of life and work of the well-known marine engineer Volodymyr Polievktovych Kostenko. Besides the author proposes approximateperiodization of historiographical research in different aspects of biography of the scientist.